2017
DOI: 10.1111/jerd.12356
|View full text |Cite
|
Sign up to set email alerts
|

Esthetics and smile‐related characteristics assessed by laypersons

Abstract: The smile variables of anterior smile line, posterior smile line, upper lip curvature, and smile index are predominant factors of smile attractiveness, which should be given priority to consider and manage in the anterior esthetic treatment plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 36 publications
3
33
1
3
Order By: Relevance
“…7, 23 Ker and colleagues 6 reported that the ideal gingival display is 2.1 mm with an acceptable range of 4 mm. Wang et al 24 found that laypersons preferred average or low smile line over high smile line "gummy smile. "…”
Section: Discussionmentioning
confidence: 99%
“…7, 23 Ker and colleagues 6 reported that the ideal gingival display is 2.1 mm with an acceptable range of 4 mm. Wang et al 24 found that laypersons preferred average or low smile line over high smile line "gummy smile. "…”
Section: Discussionmentioning
confidence: 99%
“…In dissensus to current study, attractive group had higher smile index (6.31±1.19) than unattractive group (4.64±1.17) in a Chinese study. 26 One of the explanations of the discrepancy could be attributed to ethnic variations of the studied populations.…”
Section: Discussionmentioning
confidence: 97%
“…Para realização da cirurgia de aumento de coroa clinica é fundamental que suceda uma abordagem cuidadosa, visando os padrões de beleza, onde os dentes estão intimamente ligados aos lábios, rosto e a linha do sorriso (Gonçalves, Gobbo, Fernades, Mueller & Miranda, 2017). Vários Critérios a devem observados e levados em consideração no plano de tratamento de excesso gengival, sendo elas: a dimensão da largura/comprimento dos incisivos e caninos superiores e quanto eles aparecem durante a fala e repouso, distância interlabial em repouso e as características funcionais e morfológicas do lábio superior (Seixas et al, 2011;Wang, Hu, Liang, Zhang & Chung, 2017). No paciente desse caso foi estabelecido no planejamento como modelo de gesso, um aumento de 80%, a partir da técnica de gengivectomia em bisel interno, para se obter uma proporção dentaria ideal, como também relatado no estudo de caso de Eustáquio et al (2014).…”
Section: Discussionunclassified